Uji efektivitas ekstrak daun Andong (Cordyline fruticosa) sebagai bahan antimikroba alami - Manoppo, Henky (Universitas Sam Ratulangi, 2021)
The purposed of research was to evaluate the ability of Andong leaf extract as natural antimicrobial against pathogenic bacteria, Aeromonas hydrophila. The plant was collected from yards at Kasuang Village, Tondano Disctrict of Minahasa Regency. After washing, the leaf was cut into small pieces, eased using a mortar and then extracted by maceration using alcohol 75% for 24 hours with ratio between simplicia and solvent was 1:1, 1:2, 1:4 and 1:8.Â Antimicrobial activity of the extract was examined through disc diffusion method. The results showed that leaf extract of andong was able to inhibit the growth of bacteriaÂ with strong and the sensitivity of the extract was categorized as strong.